Relationships between positive deviant behaviors and children of normal growth pattern in poorly resourced rural communities - Chitrarpita Saha; Vanisha S Nambiar (Wolters Kluwer Medknow Publications, 2018)
Background: Promotion of positive deviant behaviors (PDBs) can be crucial to bring sustainable change as these behaviors are likely to be affordable and acceptable by the wider community. Objectives: The objective of this study was to assess if any PDBs exist among poorly resourced rural mothers with young children near Vadodara. Materials and Methods: Mothers of children <5 years (n = 160) were enrolled from four rural clusters near Vadodara based on their current growth status (weight-for-age) and were categorized as PD (n = 65) and negative deviant (ND; n = 95), as per the WHO Anthro Software. Personal interviews were conducted through household (HH) visits using a semistructured questionnaire. Data were elicited on HH socioeconomic status, infant and young child feeding practices, diet pattern, and hygiene-sanitation practices. HH dietary diversity score was calculated individually after collecting data through food frequency questionnaire. Results: Mothers had several significant PDBs (P < 0.05), PD group vs. ND group, less use prelacteals to children (53% vs. 71%) and had more exclusive breastfeeding rates (44% vs. 26%), provided cleaner clothing to children (52% vs. 28%), had sufficient intra-HH food distribution (30% vs. 18%), and scored better in dietary diversity at HH level (52% vs. 28%). Conclusions: PDBs and normal growth patterns do exist in poorly resourced areas, and these mothers can be used as "change agents" by the practicing pediatricians of rural communities for improving child health and nutrition.